Characterization of an anti-fetal AChR monoclonal antibody isolated from a myasthenia gravis patient - Saxena, Abhishek; Marx, Alexander (Scientific reports, 2017)
We report here the sequence and functional characterization of a recombinantly expressed autoantibody (mAb 131) previously isolated from a myasthenia gravis patient by immortalization of thymic B cells using Epstein-Barr virus and TLR9 activation. The antibody is characterized by a high degree of somatic mutations as well as a 6 amino acid insertion within the VHCDR2. The recombinant mAb 131 is specific for the γ-subunit of the fetal AChR to which it bound with sub-nanomolar apparent affinity, and detected the presence of fetal AChR on a number of rhabdomyosarcoma cell lines. Mab 131 blocked one of the two α-bungarotoxin binding sites on the fetal AChR, and partially blocked the binding of an antibody (mAb 637) to the α-subunit of the AChR, suggesting that both antibodies bind at or near one ACh binding site at the α/γ subunit interface. However, mAb 131 did not reduce fetal AChR ion channel currents in electrophysiological experiments. These results indicate that mAb 131, although generated from an MG patient, is unlikely to be pathogenic and may make it a potentially useful reagent for studies of myasthenia gravis, rhabdomyosarcoma and arthrogryposis multiplex congenita which can be caused by fetal-specific AChR-blocking autoantibodies.